CONVEX BODIES AND GAUSSIAN PROCESSES - Vitale, Richard A (Image Analysis and Stereology, 2011)
For several decades, the topics of the title have had a fruitful interaction. This survey will describe some of these connections, including the GB/GC classification of convex bodies, Ito-Nisio singularities from a geometric viewpoint, Gaussian representation of intrinsic volumes, theWills functional in a Gaussian context, and inequalities.